2021
DOI: 10.1038/s42003-021-01873-0
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic subunit of Plasmodium falciparum casein kinase 2 is essential for gametocytogenesis

Abstract: Casein kinase 2 (CK2) is a pleiotropic kinase phosphorylating substrates in different cellular compartments in eukaryotes. In the malaria parasite Plasmodium falciparum, PfCK2 is vital for asexual proliferation of blood-stage parasites. Here, we applied CRISPR/Cas9-based gene editing to investigate the function of the PfCK2α catalytic subunit in gametocytes, the sexual forms of the parasite that are essential for malaria transmission. We show that PfCK2α localizes to the nucleus and cytoplasm in asexual and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 89 publications
1
9
0
Order By: Relevance
“…Based on the presence of a conserved amino acid motif in Pf CRK4, the pleiotropic kinase Pf CK2 was previously predicted to phosphorylate Pf CRK4 at serine 977 (Pease et al, 2013). Pf CK2 is essential for parasite proliferation in the blood stage (Hitz et al, 2021) and we found the catalytic alpha subunit of Pf CK2 (PF3D7_1108400) in the proximity of Pf CRK4 (Fig. S3, Tab.…”
Section: Discussionmentioning
confidence: 88%
“…Based on the presence of a conserved amino acid motif in Pf CRK4, the pleiotropic kinase Pf CK2 was previously predicted to phosphorylate Pf CRK4 at serine 977 (Pease et al, 2013). Pf CK2 is essential for parasite proliferation in the blood stage (Hitz et al, 2021) and we found the catalytic alpha subunit of Pf CK2 (PF3D7_1108400) in the proximity of Pf CRK4 (Fig. S3, Tab.…”
Section: Discussionmentioning
confidence: 88%
“…The P. falciparum genome encodes for 65 eukaryotic protein kinases ( 22 ), of which various members have already been described to be involved in essential processes, including egress, host cell invasion, or gametocytogenesis ( 17 , 19 , 38 , 53 ). Nevertheless, to date, only one malaria targeting kinase inhibitor has reached the phase of clinical trials: the PI4K-inhibitor MMV390048 was shown to be safe and well tolerated with high antimalarial activity against all stages of the parasitic life cycle except hypnozoites.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of work highlights the role of this enzyme class in the regulation of host cell invasion ( 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ). For instance, the physiological role of protein kinase A, casein kinase 2 (CK2) as well as glycogen synthase kinase 3 (GSK3) during the host cell invasion has been demonstrated ( 6 , 7 , 8 , 9 , 10 , 16 , 17 , 18 , 19 ). These invasion-related kinases target the cytoplasmic domains of so-called invasins ( 6 , 8 , 9 , 10 , 16 )—proteins that are secreted during the invasion process and mediate binding to surface receptors on the host cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, the SLI_PKAc_cKD transfection construct was PLOS BIOLOGY generated in 3 successive cloning steps using Gibson assembly reactions. First, the SLI_cKD precursor plasmid was generated by joining 4 fragments in a Gibson assembly reaction: (1) the plasmid backbone amplified from pUC19 (primers PCRA_F and PCRA_R) as previously described [53]; (2) the SpeI/BamHI cloning site followed by the gfp-dd sequence amplified from pD_ck2α-gfpdd [82] using primers gfp_F and dd_R; (3) the 2a-bsd sequence amplified from pSLI-BSD [35] (primers 2A_F and bsd_R); and (4) the glmS-hrp2 3 0 sequence amplified from pD_cOE (described below) (primers glmS1_F and term_R). Second, a 4-fragment Gibson assembly reaction was performed using (1) the SalI-and EcoRI-digested SLI_cKD precursor plasmid; (2) the calmodulin (PF3D7_1434200) promoter amplified from pHcamGFP-DD [53] (primers cam1_F and cam1_R); (3) the yeast dihydroorotate dehydrogenase (ydhodh) resistance gene (conferring resistance to DSM1) amplified from the pUF1-Cas-9 plasmid [83] (primers ydhodh_F and ydhodh_R); and (4) the pbdt 3 0 terminator amplified from pUF1-Cas-9 [83] (primers pbdt3_F and pbdt3_R).…”
Section: Transfection Constructsmentioning
confidence: 99%